Hubungan Ketepatan Menggosok Gigi Dengan Karies Gigi Molar Pertama Permanen Murid Kelas V Dan VI SDN Sungai Landas Kecamatan Karang Intan Tahun 2023 - Aprilia, Irma; Kisworo Utami , Naning; Sab'atul Habibah, Siti; Isnawati, Isnawati (Poltekkes Kemenkes Banjarmasin, 2024)
Dental and oral health is a problem that requires continuous handling. Most Indonesians have improper brushing habits. Most people in South Kalimantan are still not right in brushing their teeth about the right time to brush their teeth, namely the morning after breakfast and the night before going to bed The habit of brushing teeth can lead to dental caries. This study aims to determine the relationship between the accuracy of brushing teeth with permanent first molar caries for grade V and VI students of SDN Sungai Landas, Karang Intan District. The research design used was